FOOTNOTES TO DECLINE AND PROTEST: A PROFESSOR'S JOYS AND SORROWS - Townsend, Richard (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1982)
It is rare these days to find a professional who, struggling with the trivialities, disappointments, and distractions of day-to-day routine, dares to be candid about the hard time his conscience is giving him (or her). Richard Townsend has never been one to dodge candour; his discussion here returns repeatedly to the difficulties a modern professor has in matching the expectations of the role, public and private, in his field. His self-assigned task is to find lessons from his experience, and models among his colleagues, so that he may surmount those difficulties and come closer to the ideal. Along the way, some unexpected lights are cast on the seemingly intractable problems occasioned by the closing down of schools, in a manner suggesting a provocative postscript to the articles in this issue. RÉSUMÉ Il est plutôt rare aujourd'hui de rencontrer un professionnel qui, devant les banalités, les déceptions et les distractions de la vie quotidienne, ose demeurer sincere face aux tracas que lui cause sa conscience. Richard Townsend n'est pas du genre à éluder la question de la sincérité; sa dissertation en revient toujours aux difficultés qu'un professeur d'aujourd'hui a à répondre aux attentes du rôle, à la fois public et privé, qu'il est tenu de jouer. La tâche à laquelle il doit s'astreindre consiste à tirer des leçons de son expérience, à trouver des modèles parmi ses collègues afin de surmonter ces difficultés et d'approcher de la situation idéale. En cours de route, certaines lueurs imprévues viennent éclairer les problèmes apparemment insolubles que provoque la fermeture de tant d'écoles.